Characterizing Gut Physiology and Myeloid Cell Populations by Age and Sex - Caldwell, Alice (My University, 2025)
Gut physiology changes with age, but whether these age-related changes contribute to unhealthy aging is unclear. Previous work found that gut barrier function is impaired with age in mice and coincides with an increase in systemic inflammation, but more recently, we discovered that female guts become ‘leakier’ with age than male guts. We hypothesize that deterioration of intestinal barrier structure increases inflammation in the gut due to activation of myeloid cell mediated responses. We investigated gut structure by histological assessment and RT-qPCR analyses using colon and ileum tissues derived from groups of old or young, male or female, specific pathogen-free mice. We found no structural changes in the colon and ileum, and no changes in tight junction protein gene expression in the colon with age in either sex. Second, we investigated how gut permeability influenced intestinal inflammation by observing changes in intestinal macrophage subsets by flow cytometry. We identified an increase in the frequency of monocyte-derived CD4-TIM-4- macrophages with age in the colon for both sexes, indicating increased macrophage replenishment from recruited peripheral monocytes. CD4-TIM-4- macrophages are primarily associated with pro-inflammatory functions, and their replenishment is indicative of inflammation in the colon. This age-dependent increase in the frequency of CD4-TIM-4- macrophages was not observed in TNF-/- mice, highlighting the role of TNF in age dependent intestinal inflammation. We were unable to elucidate the sex-specific effects of increased intestinal permeability on intestinal inflammation in females. Further investigation is required to decipher the mechanisms by which aging trajectory is influenced by gut permeability and associated inflamm-aging. Such investigation may identify targets for novel preventative strategies to prolong late-life health. To our knowledge, this is the first investigation exploring sex-dependent changes in gut physiology with age.
The Aging Gut and Inflammation
Keywords: Immunology; Gut; Aging; Inflammation